Limited Cost Benefit of Lateral Interbody Fusion for Adult Spinal Deformity Surgery. Issue 1 (1st January 2021) - Yamamoto, Tatsuya; Yagi, Mitsuru; Suzuki, Satoshi; Nori, Satoshi; Tsuji, Osahiko; Nagoshi, Narihito; Okada, Eijiro; Fujita, Nobuyuki; Nakamura, Masaya; Matsumoto, Morio; Watanabe, Kota
Abstract : Study Design: Retrospective case series. Objective: The aim of this study was to compare the utility and cost-effectiveness of multilevel lateral interbody fusion (LIF) combined with posterior spinal fusion (PSF) (L group) and conventional PSF (with transforaminal lumbar interbody fusion) (P group) in adult spinal deformity (ASD) surgery. Summary of Background Data: The clinical and radiographic outcomes of multilevel LIF for ASD have been reported favorable; however, the cost benefit of LIF in conjunction with PSF is still controversial. Methods: Retrospective comparisons of 88 surgically treated ASD patients with minimum 2-year follow-up from a multicenter database (L group [n = 39] and P group [n = 49]) were performed. Demographic and radiographic data, health-related quality of life (HRQoL), and the direct hospitalization cost for the initial surgery and 2-year total hospitalization cost were analyzed. Results: Analyses of sagittal spinal alignment showed no significant difference between the two groups at baseline and 2 years post-operation. Surgical time was longer in the L group (L vs. P: 354 vs. 268 minutes, P < 0.01), whereas the amount of blood loss was greater in the P group (494 vs. 678 mL, P = 0.03). The HRQoL was improved similarly at 2 years post-operation (L vs. P: SRS-22 total score, 3.86 vs. 3.80, P = 0.54), with comparable revision rates (L vs. P: 18% vs. 10%, P = 0.29). The total direct cost of index surgery was significantly higher in the L group (65, 937 vs. 49, 849 USD, P < 0.01), which was mainly due to the operating room cost, including implant cost (54, 466 vs. 41, 328 USD, P < 0.01). In addition, the 2-year total hospitalization cost, including revision surgery, was also significantly higher in the L group (70, 847 vs. 52, 560 USD, P < 0.01). Conclusion: LIF with PSF is a similarly effective surgery for ASD when compared with conventional PSF. However, due to the significantly higher cost, additional studies on the cost-effectiveness of LIF in different ASD patient cohorts are warranted. Level of Evidence: 3 Abstract : LIF with PSF is a similarly effective surgery for ASD when compared with conventional PSF. However, due to the significantly higher cost of LIF, which is mainly due to the operating room cost (including implant cost), additional studies on the cost-effectiveness of LIF in different ASD patient cohorts are warranted.